2011
DOI: 10.1029/2010jb007837
|View full text |Cite
|
Sign up to set email alerts
|

Repeated fluid-transfer episodes as a mechanism for the recent dynamics of Campi Flegrei caldera (1989–2010)

Abstract: We have analyzed a multiparametric data set of seismological, geodetic and geochemical data recorded at Campi Flegrei caldera since 1982. We focus here on the period 1989–2010 that followed the last bradyseismic crisis of 1982–1984. Since then, there have been at least five repeated minor episodes of ground uplift accompanied by seismicity. We have reanalyzed old paper and digital seismic data sets dating back to 1982. The paper recordings show evidence of long‐period events in January 1982 and March 1989, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
151
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(161 citation statements)
references
References 78 publications
9
151
1
Order By: Relevance
“…However, in calderas the acceleration of these phenomena (ground deformation, degassing and seismicity) does not necessarily culminate in an eruption (Newhall and Dzurisin, 1988;Biggs et al, 2014;Acocella et al, 2015). Examples are the non-eruptive unrest at Campi Flegrei caldera (Italy) during 1968-1970and 1982-1984(Del Gaudio et al, 2010D'Auria et al, 2011), Long Valley (California) during 1978-2000(Hill, 2006, Rabaul (Papua New Guinea) in 1984 (McKee et al, 1984), Sierra Negra (Galápagos Islands, Ecuador) in 1996 (Chadwick et al, 2006), Yellowstone (USA) between 2004 and 2010 (Chang et al, 2010), Santorini (Greece) in 2011-2012 (Newman et al, 2012;Lagios et al, 2013), which were accompanied by significant variations in the monitoring parameters but were not followed by an eruption (Segall, 2013;Acocella et al, 2015). In particular, in the last decades, Campi Flegrei has shown a total uplift of more than 3 m (Bianchi et al, 1987), followed by subsidence (Del Gaudio et al, 2010), as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, in calderas the acceleration of these phenomena (ground deformation, degassing and seismicity) does not necessarily culminate in an eruption (Newhall and Dzurisin, 1988;Biggs et al, 2014;Acocella et al, 2015). Examples are the non-eruptive unrest at Campi Flegrei caldera (Italy) during 1968-1970and 1982-1984(Del Gaudio et al, 2010D'Auria et al, 2011), Long Valley (California) during 1978-2000(Hill, 2006, Rabaul (Papua New Guinea) in 1984 (McKee et al, 1984), Sierra Negra (Galápagos Islands, Ecuador) in 1996 (Chadwick et al, 2006), Yellowstone (USA) between 2004 and 2010 (Chang et al, 2010), Santorini (Greece) in 2011-2012 (Newman et al, 2012;Lagios et al, 2013), which were accompanied by significant variations in the monitoring parameters but were not followed by an eruption (Segall, 2013;Acocella et al, 2015). In particular, in the last decades, Campi Flegrei has shown a total uplift of more than 3 m (Bianchi et al, 1987), followed by subsidence (Del Gaudio et al, 2010), as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…2 in D'Auria et al, 2011), periodically interrupted by small (centimetre-scale) and short-lived (months) uplifts in , 2000(e.g. Lanari et al, 2004Bianco et al, 2004;D'Auria et al, 2011(e.g. Saccorotti et al, 2007Trasatti et al, 2008;D'Auria et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Between 12 and 3.8 ka there were three eruptive episodes followed by a long period of quiescence until the last eruption of Monte Nuovo in 1538 CE (Di Vito et al, 1999). During the last decades CFc is subjected to seismic activity, gas emissions and intense ground deformations (Chiodini et al, 2001;D'Auria et al, 2011). Recent events of uplift occurred in 1950-1952, 1969-1972, and in 1982-1984(Del Gaudio et al, 2010 Figure 7).…”
Section: Campi Flegreimentioning
confidence: 99%